Macromolecular medium repairing agent and oil and gas pipeline repairing method based on same

By developing a combination of medium-weight polymer repair agents and ultra-high molecular weight polyethylene fiber materials, and using compression molding technology, the problems of unstable performance and insufficient contact of repair agents in existing oil and gas pipeline repair methods have been solved, achieving high efficiency and durability. Excellent repair effect and low-cost construction process.

CN119331383APending Publication Date: 2025-01-21ZHENGZHOU XINRUI PETROLEUM ENG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411453541.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the existing oil and gas pipeline pressure repair methods, the repair agent has unstable performance and insufficient contact with the composite material, resulting in a short-lasting repair effect and requires frequent maintenance, which increases the cost and difficulty.

Method used

A medium-weight polymer repair agent was developed. By fully mixing component A and component B in a ratio of 4 to 10:1, combined with ultra-high molecular weight polyethylene fiber material, a composite repair layer was formed using molding technology to enhance the The adhesive performance and construction process of the repair agent.

Benefits of technology

This method is used under low temperature conditions. The stability of the repair agent is better, the repair effect is significantly improved. The molecular chain structure density of the mold pressure repair layer can effectively suppress the leakage, the service life is long, and the construction is safe and fast without fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331383A_ABST
    Figure CN119331383A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of pipeline reinforcement, in particular to a high-molecular medium repairing agent and an oil and gas pipeline repairing method based on the high-molecular medium repairing agent. According to the repairing method, the compression molding technology is completed by adding nanoscale boron carbide powder, carboxyl liquid nitrile rubber, phenyl glycidyl ether, an ultra-high molecular weight polyethylene fiber material and a modified polyamide material into a resin raw material with the epoxy equivalent being 300 or above and carrying out compression molding through a prefabricated compression molding tool and a pipeline body. The repairing agent is stable in performance and can still have a good curing effect at a low environment temperature, meanwhile, the repairing agent is matched with the repairing method, on one hand, the good repairing effect on the pipeline can be achieved, on the other hand, the bearing force of the repaired part of the pipeline is two times or above of the normal operation pressure of the pipeline, and the repairing effect is good. After the pipeline is completely invalid, a good leaking stoppage effect can be achieved, and the plugging agent is convenient to use in engineering practice.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pipeline reinforcement, and in particular to a high-molecular-weight repair agent and an oil and gas pipeline repair method based thereon. Background Art

[0002] During the operation of long-distance pipelines, defects caused by corrosion from internal media and external environment bring potential safety hazards to pipeline operation, so they need to be reinforced and repaired. Hot work repairs require the pipeline to be shut down and vented, which takes a lot of time and has high maintenance costs. Therefore, the existing methods are mostly carried out under pressure repair while the pipeline is in operation, which does not affect the normal use of the pipeline and can effectively save time and maintenance costs.

[0003] Existing pressure repair technologies mostly use a repair method that combines composite materials with repair agents. During the process, the composite material is wrapped around the outer surface of the defective pipe and together with the repair agent, a composite repair layer is formed. This method can achieve reinforcement and repair of pipeline defects and play a certain role in plugging leaks after the pipeline fails completely. However, it has been found in long-term practice that the plugging effect of this repair method is not stable and lasting. Even if the method of winding the composite material is optimized, it is still easy to fail after a period of use and needs to be repaired again. The second repair is not only difficult but also increases the cost of labor and material resources, which brings difficulties to the actual repair work.

[0004] Research has found that there are two main reasons why the above method has poor results in practice: 1. The existing repair agent has unstable performance during use and is easily affected by external conditions, such as incomplete grinding, temperature, humidity, sand and gravel particles, etc.; 2. The repair agent is not in sufficient contact with the composite material and cannot achieve a good repair effect; Therefore, in long-term practical exploration, we have developed a new repair agent and a pipeline repair method based on it, so as to solve the problem of poor repair effect of existing repair agents and repair methods. Summary of the invention

[0005] The purpose of the present invention is to provide a high molecular weight repair agent and an oil and gas pipeline repair method based thereon, so as to solve the problem that the existing repair agents and repair methods have poor effects.

[0006] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a high molecular weight repair agent, including component A and component B;

[0007] The component A comprises 100-300 parts of epoxy resin, 10-100 parts of phenyl glycidyl ether, 1-20 parts of carboxyl liquid nitrile rubber, and 10-50 parts of boron carbide powder;

[0008] The B component comprises 100-200 parts of polyamide resin, 50-150 parts of ethylenediamine, 1-20 parts of thiourea and 1-10 parts of triacetin.

[0009] Furthermore, the epoxy resin in the component A is a resin with a medium epoxy value, and the boron carbide powder is a nano boron carbide powder;

[0010] The preparation of the A component comprises the following steps:

[0011] S1. Take 200 parts of a resin with a medium epoxy value and 50 parts of phenyl glycidyl ether; pour them into a reaction kettle with a constant temperature of 80°C, stir them thoroughly for 4 hours and keep the temperature constant for 30 minutes;

[0012] S2, take 10 parts of carboxyl liquid nitrile rubber, raise the temperature to 100°C, stir thoroughly for 3 hours, and then lower the temperature by 20°C every 2 hours;

[0013] S3. After 6 hours, add 20 parts of nano boron carbide powder, keep the temperature at 40°C, stir for 2 hours, place in a defoaming box, keep the temperature at 40°C for 24 hours to eliminate excess bubbles, and complete the modulation process of component A.

[0014] Furthermore, the polyamide resin in the B component is a low molecular weight polyamide resin 650;

[0015] The preparation of the B component comprises the following steps:

[0016] S1. Take 150 parts of low molecular weight polyamide resin 650 and 100 parts of ethylenediamine, put them into a reaction kettle at one time, heat the temperature to 120°C, stir at medium speed, and stir for 4 hours;

[0017] S2, naturally cool to 70-80°C, add 10 parts of thiourea and 5 parts of triacetin, keep the temperature at 70°C, and stir at medium speed;

[0018] S3. When no ammonia odor escapes from the system, stop heating and stirring, cool to room temperature, discharge the material, and seal for storage, thus completing the preparation process of component B.

[0019] Furthermore, when the repair agent is used, component A and component B are fully and evenly mixed in a ratio of 4 to 10:1.

[0020] The oil and gas pipeline repair method based on the above-mentioned repair agent comprises the following steps:

[0021] S1. Using ultra-high molecular weight polyethylene fiber material as the skeleton, design and determine the number of winding layers and molded thickness at the pipeline repair site;

[0022] S2. Perform surface treatment on the pipe at the repaired part;

[0023] S3, fully and evenly mix the components A and B of the repair agent, spread the ultra-high molecular weight polyethylene fiber material flat, and evenly apply the mixed repair agent on the ultra-high molecular weight polyethylene fiber material until the ultra-high molecular weight polyethylene fiber material is fully soaked;

[0024] S4. Level the fully soaked ultra-high molecular weight polyethylene fiber material and wrap it around the outer surface of the pipe at the repaired part with appropriate force until the number of winding layers required by the construction design is reached;

[0025] S5. Install the molding device to mold the wound parts. After the molding is completed, remove the molding device and conduct acceptance.

[0026] Furthermore, in the S1, an 8mm through hole is opened in the pipeline body to simulate the pressure bearing data of the molded repair layer on the pipeline medium after the corrosion body fails in the pipeline; the relationship between the molded thickness and the pressure bearing is calculated by the three-dimensional nonlinear finite element method, and then the number of winding layers and the molded thickness of the ultra-high molecular weight polyethylene fiber material are determined through a hydrostatic pressure blasting test.

[0027] Furthermore, in S2, before surface treatment is performed on the pipe at the repaired part, the defect points of the repaired part need to be verified, and the surface treatment of the pipe can be performed only after the verification is consistent; the surface treatment of the pipe includes stripping of the old anti-corrosion layer and polishing of the pipe surface.

[0028] Furthermore, in the above S4, before winding the ultra-high molecular weight polyethylene fiber material, a filling material is prepared and applied to the concave part of the steel pipe surface to repair the defective part until the surface is flat; the two sides of the weld root should be filled with the filling material to make the surface near the weld transition smoothly and avoid hollowing when the ultra-high molecular weight polyethylene fiber material is wound due to the weld being too high;

[0029] The filling material comprises component A, S-grade glass fiber and component B, component A: S-grade glass fiber: component B = 2:1.5:1, and the component A, S-grade glass fiber and component B are fully mixed.

[0030] Furthermore, in the S4, during the winding process, the axial overlap length of the ultra-high molecular weight polyethylene fiber material should be 20% to 40% of its width, and the circumferential overlap length should be no less than 200 mm; when the circumferential winding length is insufficient, the overlap length of the ultra-high molecular weight polyethylene fiber material continued to be wound should be no less than 200 mm.

[0031] Furthermore, in the S5, the molding device includes a tightening reel and a retaining ring. The tightening reel is wound on the pipe and pre-tightened by bolts. The retaining rings are arranged at both ends of the tightening reel to prevent the disorderly flow of the repair agent during the molding process. Before molding, a release agent is coated on the inner side of the retaining ring and the tightening reel.

[0032] Beneficial effects of the present invention:

[0033] 1. The repair agent can be used under low temperature conditions, with better stability, which can effectively improve the repair effect;

[0034] 2. The molded molecular chain structure has a high density, high tensile shear performance with steel, and a predetermined molded thickness, which can effectively meet the design requirements and play a role in inhibiting leakage;

[0035] 3. The molded repair operation is safe and rapid. The molded repair does not require welding or fire, and the repair is carried out under pressure. The construction process does not require pressure reduction or production suspension, and no large equipment is required.

[0036] 4. The reinforcement repair layer is an insulator, which protects the pipeline from electrochemical corrosion; it is corrosion-resistant, aging-resistant and has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of the molded stress-bearing surface of the weftless fabric in Example 1 of the present invention;

[0038] Figure 2 is a schematic diagram of openings on the surface of a pipeline in Example 1 of the present invention;

[0039] Figure 3 is a schematic structural diagram of a molding device in Example 1 of the present invention;

[0040] Figure 4 It is a schematic diagram of the construction process flow in Example 1 of the present invention.

[0041] The names corresponding to the marks in the figure are:

[0042] 1. Tightening drum; 2. Connecting part; 3. Bolt; 4. Retaining ring; 5. Pipeline. DETAILED DESCRIPTION

[0043] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0044] The pressure bearing capacity of a pipeline is affected by many factors. In general, the following equation can be used to express the pressure bearing capacity of a pipeline:

[0045] P=(2*S*t / D)*F*E*T

[0046] Where:

[0047] P represents the design pressure; S represents the minimum yield strength of the steel pipe; T represents the pipe wall thickness; D represents the pipe diameter; F represents the design coefficient; E represents the welding coefficient; and T represents the temperature coefficient.

[0048] During the operation of the pipeline, circumferential stress exists due to the internal pressure. If a part of the pipe wall surface is damaged or thinned, the damaged part will be subjected to greater pressure than the normal part, and may even exceed the safety limit and cause a pipe burst.

[0049] The compression molding repair technology is to wrap the composite repair material around the outer surface of the defective pipe, and together with the repair agent, form a composite repair layer, and then install the customized mold on the uncured repair layer, pre-tighten the locking device of the mold to make it reach the predetermined repair thickness, and remove the mold after curing to complete the repair; after the molded repair layer is completed, part of the stress borne by the defective part of the pipe will be transferred to the molded repair layer, so that the stress borne by the defective part of the pipe is always under the safety limit. Once the pipeline body fails, the molded composite material and the pipeline body become completely integrated, so that the force it bears is more than twice the operating pressure of the pipeline, completing the role of suppressing leakage and ensuring the safe operation of the pipeline.

[0050] The high molecular weight medium-weight repair agent is the connecting material between the steel pipe and the ultra-high molecular weight polyethylene fiber. It needs to have sufficient bonding strength and good construction processability. In addition, this repair agent should also have good resistance to cathodic stripping. For defective pipelines that are reinforced and repaired after molding, the molded repair layer has good bonding strength with the pipe body. Due to the effect of the pipeline ground potential or cathodic protection potential, the general repair layer of the pipeline is prone to fall off or loosening over time, especially at the edge of the reinforcement layer or in defective areas. The high molecular weight medium-weight repair agent is prepared using a special process, and then molded using a mold. After molding, the molecular chain structure of the repair layer is more compact, and the bonding strength with the steel pipeline is stronger, which can effectively resist the loosening or stripping of the defective repair caused by external current.

[0051] The repair agent of the present invention is formed by combining two components A and B; Group A selects a resin with a medium epoxy value as a base material, and has the advantages of low curing volatiles, small shrinkage, high bonding strength, simple bonding process and good electrical properties; the reactive functional group contained in the carboxyl liquid nitrile rubber is an epoxy group, and liquid rubbers with different epoxy group contents have different effects on the impact strength of the resin casting body and the tensile shear performance of the adhesive. Adding carboxyl liquid nitrile rubber can effectively increase the impact strength of the repair layer and increase its tensile shear strength by 150%; nano-scale boron carbide powder has high chemical potential, neutron absorption, wear resistance and semiconductor conductivity, and is one of the substances that is stable to acid. It is stable in concentrated or dilute acid or alkali aqueous solutions. The material and epoxy are fully stirred and fused, and then play a reinforcing role.

[0052] Component B uses ethylenediamine, thiourea and triacetin to modify the polyamide resin. The main feature of the modified polyamide resin is that it can achieve rapid curing at an ambient temperature of -25°C in the north. Traditional curing agents generally do not cure or cannot completely cure at temperatures below 0°C, which seriously affects the strength of the composite material.

[0053] The molding equipment uses the pipe body as support, annular clamps at both ends, and the molding thickness is set by bolt tightening method. An annular stainless steel plate is made as a package, and the clamp is pre-tightened by the screw at the connection to achieve the pre-molding thickness; non-woven ultra-high molecular weight polyethylene fiber cloth (repair material) is used as the skeleton. The molecular content of the non-woven cloth is more than 1.5 million. It is a fiber material with super tensile strength. Its molecular chain is very long and arranged in an orderly manner, and there is a very strong interaction force between molecules, which enables the fiber to better disperse and withstand force when subjected to force, thereby increasing the tensile strength and specific strength of the fiber.

[0054] Example 1

[0055] In this embodiment, defects in a gas pipeline of a northern oil production plant were repaired. The ambient temperature during operation was -25 to -10°C, the pipe diameter was 377mm, the design pressure was 10MPa, and the pipeline material was L245NB. Compression molding repair was performed on 60 defect detection locations. The compression molding repair layer was designed to withstand a pressure of 15MPa. After the repair was completed, it was accepted and was fully qualified.

[0056] The specific repair steps are as follows:

[0057] 1. Molding thickness design

[0058] The thickness of the molded repair layer is determined by a hydrostatic blasting test. The order of the non-woven fabric (repair material) follows the stress response mechanism of the pipeline, and the winding direction of the non-woven fabric and the molded stress surface (such as Figure 1 ). The defective part of the pipeline is first repaired with a repair agent, and after the repair, there will be no dents at the defective point.

[0059] The pipe used in this embodiment has an outer diameter of 377 mm, a wall thickness of 6 mm, and a steel grade of X52. An electric drill is used to drill an 8 mm through hole ( Figure 2 ), simulates the pressure bearing data of the molded repair layer on the pipeline medium after the corrosion body inside the pipeline fails.

[0060] The relationship between the molded thickness and the bearing pressure was calculated by the three-dimensional nonlinear finite element method. The thickness of each layer of winding was controlled to 0.6 mm. The relationship between the molded thickness and the bearing pressure was obtained through experiments, and then the molded thickness was determined through a hydrostatic blasting test (Table 1).

[0061] Table 1 Hydrostatic Burst Test Table

[0062]

[0063] Through the molded repair layer test, it was found that after the number of winding layers reached 25 and the thickness of the repair layer after molding reached 10mm, the pressure-bearing effect of the molded repair layer could reach the expected target pressure of 20MPa. If the thickness is increased again, there will be no significant improvement in the pressure resistance. The winding thickness is generally 3-5mm higher than the actual required molded repair layer. Leaving enough molding volume can improve the density of the molded repair layer, thereby improving the pressure-bearing effect after molding.

[0064] 2. Installation process

[0065] 2.1 Defect Point Verification

[0066] All defect points that need to be molded should be verified using relevant testing technology before construction. The specific operations are as follows:

[0067] 1. Confirm the location of the defect point. Confirm the approximate location of the defect point according to the technical briefing, and use PCM or other testing equipment to accurately locate the defect point;

[0068] 2. Investigate the defect data, pipeline data, operation data, environmental data, etc. of the pipeline to be repaired. For metal defect points, geometric dimension measuring tools, ultrasonic thickness gauges, etc. should be used to verify the defect information and record it;

[0069] 3. Video recorders should be used to capture video data during the verification process;

[0070] 4. External corrosion defect measurement

[0071] For external corrosion defects, the axial length, width and clock position shall be directly measured with a micrometer, vernier caliper, etc. with a measurement accuracy of not less than 1mm, and the error shall be no greater than 1mm. The maximum depth of external corrosion shall be directly measured with a vernier caliper with a measurement accuracy of not less than 0.1mm, and the error shall be no greater than 0.1mm. The construction record documents shall be filled in strictly according to the measurement results.

[0072] The maximum length, maximum depth and width of the defect point should be consistent with the intelligent detection results. If the measurement results deviate too much from the intelligent detection results, they should be reviewed again. If there is still a large deviation after the second review, the measurement results shall prevail, and the on-site supervisor shall be notified to jointly determine the review and repair plan.

[0073] When measuring the maximum longitudinal length L, if the distance between two corrosion pits is less than 25 mm, they are considered to be the same corrosion area; when measuring the maximum corrosion circumference C, if the distance between two corrosion pits is less than 6 times the wall thickness, they are considered to be the same corrosion area.

[0074] 5. Internal corrosion defect measurement

[0075] For internal corrosion defects, ultrasonic thickness gauges are used to measure the depth, axial length and width of the defects, and the clock position of the defects is recorded. When using an ultrasonic thickness gauge for measurement, a measurement grid must be drawn on the surface of the pipeline, and measurements must be made grid by grid, and the construction record file must be filled in strictly according to the measurement results. At least three groups of data should be measured for each defect point; and the two defect location points adjacent to the defect point must be approved, and the measurement data of the three defect points must be completely consistent with the intelligent detection results before they can be finally determined; after the defect point is determined, the ultrasonic thickness gauge should be used to accurately calibrate the range of the defect point, and the range of the defect should be marked on the outer surface of the pipeline.

[0076] Ultrasonic measurement requires that the metal surface to be measured is basically smooth and free of debris. When measuring, apply a coupling agent with high acoustic impedance between the probe and the metal surface to reduce sound wave leakage loss. Each test position should be measured once in a mutually perpendicular direction as much as possible. Select the probe according to the pipe diameter and temperature conditions.

[0077] 7. Sag measurement

[0078] Equip sufficient equipment and instruments, and operators who can use them correctly, measure the length and width of the depression, and keep corresponding records.

[0079] Contour gauge measurement: Divide the outer surface of the depression into equal intervals along the circumferential direction, and use the contour gauge to fit closely to the outer surface of the depression along the axial direction at different dividing lines in turn. According to the shape of the contour gauge, the contour of the depression on different cross sections is obtained to depict the morphology of the depression.

[0080] Profiling ruler measurement: Divide the outer surface of the depression into equidistant grids, use a profiling ruler to measure the deformation depth at each grid point, and depict the morphology of the depression based on the measurement data.

[0081] Digital caliper with long straight bridge to measure:

[0082] a. Place the straight bridge ruler along the longitudinal axis with the deepest depression as the center;

[0083] b. Measure the distance between the ruler and the deepest depression;

[0084] c. If the pit is located at the elbow (longitudinal curvature, regional curvature) (see the following section for details), adjust the measurement depth as follows;

[0085] d. Maximum pit depth = measured value - concave surface;

[0086] e. Use a ruler to determine the shoulder where the change in curvature ends at each end of the dimple;

[0087] f. The distance to the normal profile of the pipeline should be measured, that is, the plane related to the ellipse is extended to the position of the normal profile.

[0088] 2.2 Anti-corrosion layer stripping and pipeline surface treatment

[0089] 1. Anti-corrosion layer peeling

[0090] a. The removal of the old anti-corrosion layer should be carried out by a combination of power, manual, hydraulic, solvent and other methods. After removal, there should be no obvious old anti-corrosion layer and primer residue on the surface of the pipe body, and the removal process should not damage the metal of the pipe body;

[0091] b. Effectively handle the peeled anti-corrosion layer and removed anti-corrosion primer, and do not litter or place them randomly to pollute the environment;

[0092] c. The axial stripping distance at both ends of the defect point should be at least 100mm longer than the axial repair length;

[0093] d. After removing the anti-corrosion layer, the defect size should be verified using an ultrasonic thickness gauge and a vernier caliper (including a depth measuring ruler). Sufficient equipment and instruments should be provided, as well as operators who can use them correctly.

[0094] 2. Pipeline surface treatment

[0095] a. Install an automatic grinding device on the pipeline. After the power is turned on, push and rotate the grinding device to remove rust and grind. The use of the automatic grinding device can eliminate grinding dead corners and achieve a unified grinding standard;

[0096] b. After the outer surface of the pipeline is treated, clean, dry, oil-free compressed air should be used to remove sand, dust, rust powder, etc. on the surface of the pipeline. The dust level should reach Level 2 as specified in the current national standard "Surface cleanliness assessment test for steel surface treatment before coating Part 3: Dust assessment on steel surface before coating (pressure-sensitive adhesive tape method)" (GB / T18570.3);

[0097] c. The dirt on the surface of the outer anti-corrosion layer within 500mm around the defect and that needs to be wrapped circumferentially should be cleaned and polished. The edge of the anti-corrosion layer in the defect area should be processed into a slope surface. The slope treatment angle of the thick coating should be 30-45°;

[0098] d. After grinding, anchor pattern treatment is performed according to the actual situation. The anchor pattern depth is recommended to be 40μm to 90μm;

[0099] e. Before repairing, the polished area must be treated with cleaning agents and other materials to ensure the cleanliness of the repaired surface;

[0100] f. Subsequent reinforcement and anti-corrosion work should be carried out within 2 hours. If it exceeds the prescribed time, the surface rust removal should be carried out again.

[0101] 2.3 Moulding repair work

[0102] 1. Before installing the molding device, the axial length of the defect must be checked again to ensure that the defect is located in the middle of the non-woven fabric material, and the installation position of the non-woven fabric material is marked at the ground position where the pipeline is located.

[0103] 2. Mix the repair agent thoroughly and evenly according to the repair agent ratio requirements, and then use the repair agent to fill the defective parts and weld parts to ensure that the defective parts and weld parts are flat;

[0104] Repair of defects on the surface of steel pipe:

[0105] a. Prepare molded repair agent and filling materials according to the temperature and humidity of the construction site.

[0106] The filling material consists of component A, S-grade glass fiber and component B. Component A: S-grade glass fiber: B = 2:1.5:1. Mix component A, S-grade glass fiber and B evenly.

[0107] b. Measure and mix the prepared filling materials evenly, determine the amount and control the use time according to the actual temperature;

[0108] c. Apply the filling material to the concave parts (honeycomb, pockmarks, small holes, etc.) on the surface of the steel pipe and repair until the surface of the defective part is flat;

[0109] d. Filling materials should be used on both sides of the weld root to ensure a smooth transition of the surface near the weld to avoid hollowing caused by the entanglement of the molded material due to the weld being too high. The vertical distance between the edge of the filling area and the weld is about 5 cm.

[0110] 3. Use a thermometer to measure the surface temperature of the pipe. If the pipe mark temperature is higher than 80°C, the temperature resistance of the composite agent should be adjusted (appropriately reduce the proportion of component B);

[0111] 4. After setting the molding length, install the retaining rings on both sides of the molding set. The retaining rings not only play the role of molding length, but also can prevent the repair agent from flowing disorderly during the molding process;

[0112] 5. Under the working conditions of this embodiment, the repair agent components A and B are mixed in a ratio of 4 / 1 and stirred evenly. Then, the ultra-high molecular weight polyethylene fiber material is spread flat, and the mixed repair agent is applied to the high molecular weight polyethylene fiber material using a roller or a brush until the high molecular weight polyethylene fiber material is fully soaked.

[0113] The preparation process of component A is as follows:

[0114] a. Take 200 parts of medium epoxy resin and 50 parts of phenyl glycidyl ether; pour into a reactor with a constant temperature of 80°C, stir thoroughly for 4 hours and keep the temperature constant for 30 minutes;

[0115] b. Take 10 parts of carboxyl liquid nitrile rubber, raise the temperature to 100°C, stir thoroughly for 3 hours, and then lower the temperature by 20°C every 2 hours;

[0116] c. After 6 hours, add 20 parts of nano boron carbide powder, keep the temperature at 40°C, stir for 2 hours, place in a defoaming box, keep the temperature at 40°C for 24 hours to eliminate excess bubbles, and complete the modulation process of component A.

[0117] The preparation process of component B is as follows:

[0118] a. Take 150 parts of low molecular weight polyamide resin 650 and 100 parts of ethylenediamine, put them into the reaction kettle at one time, heat the temperature to 120°C, stir at medium speed, and stir for 4h;

[0119] b. Cool naturally to 70-80°C, add 10 parts of thiourea and 5 parts of triacetin, keep the temperature at 70°C, and stir at medium speed;

[0120] c. When no ammonia odor escapes from the system, stop heating and stirring, cool to room temperature, discharge the material, and seal for storage, thus completing the preparation process of component B.

[0121] The repair agent component B of the present invention has good curing performance under low temperature conditions. The repair agent of the present invention is compared with the traditional D230 curing agent. The experimental sample is developed into a preset mold with a mold thickness of 2 mm and a length of 300 mm. The data are as follows:

[0122] Table 2 Curing parameters of component B of the present invention and D230

[0123]

[0124] After the experimental sample is cured, the sample is taken out for demoulding. The sample using the curing agent of component B of the present invention has been completely cured, and the surface is demoulded cleanly without adhesion; the curing agent D230 not only has adhesion, but also has obviously insufficient hardness. After mechanical property analysis, the data of the AB component of the present invention meets the technical standards, and the performance of the D230 curing agent is obviously attenuated. The technical parameters are compared as follows:

[0125] Table 3 Performance comparison of the composite material of the present invention and the composite material of the traditional curing agent

[0126]

[0127] It can be concluded from the elongation at break and water absorption that D230 cannot be completely cured at low temperature, the hardness cannot reach the elongation at break, the density will be longer, and the density will be relatively soft.

[0128] 6. Level the fully soaked high molecular weight polyethylene fiber material and wrap it around the outer surface of the pipe at the repaired part with appropriate force until the number of layers required by the construction design is reached. In this embodiment, the number of reinforcement layers is not less than 25 layers to be qualified;

[0129] 7. The axial overlap length of ultra-high molecular weight polyethylene fiber should be 20% to 40% of the fiber cloth width, and the circumferential overlap length should not be less than 200mm;

[0130] 8. When the length of the circumferentially wound high molecular weight polyethylene fiber cloth is insufficient, the overlapping length of the continuously wound high molecular weight polyethylene fiber cloth should be no less than 200 mm;

[0131] 9. Use a release agent to coat the surface of the retaining ring. It can also be coated in advance before installation. It is forbidden to coat the release agent on the molded section;

[0132] 10. Wrap the preset molded length to 25 layers, sleeve the molded tightening reel onto the composite layer, and pre-tighten the composite layer ( Figure 3 ), molded to a thickness of 10 mm (i.e., molded repair layer), and a release agent must be applied to the inside of the molded tightening roll before molding to facilitate final demoulding;

[0133] like Figure 3 As shown, in this embodiment, the molding device includes a tightening reel 1 and a retaining ring 4. The tightening reel 1 is rolled up on the pipe. Connecting parts 2 are provided on both sides of the tightening reel 1. Bolts 3 are connected through the connecting parts 2. The tightening reel 1 is rolled up and fixed on the pipe through the pre-tightening bolts 3. Retaining rings 4 are installed on the pipes on both sides of the tightening reel 1. The retaining rings 4 include two upper and lower half rings and are tightly fixed to the two ends of the tightening reel 1 through connecting bolts.

[0134] 11. At -25 to -10°C, the initial curing time is generally 4 to 8 hours. During the curing period, the repaired area must be kept clean and dry;

[0135] a. After the molded repair construction is completed, in order to achieve the best molded repair layer effect in the operation area, the molded device shall be removed after 24 hours;

[0136] b. During the curing period, the working area should be shielded with plastic film to prevent sand or rain;

[0137] c. After the molding construction is completed, the time for backfilling is 1-3 days. The specific time depends on the ambient temperature and the temperature of the conveying medium inside the pipeline. As long as the surface is dry and solidified (no marks left by nail carving), backfilling can be done;

[0138] d. If the pipeline is depressurized before repair, the operating pressure of the pipeline must be restored after the molding solidifies.

[0139] 12. After the mold repair is completed, backfill the work pit to restore the original topography and ensure that the work is completed and the site is clean.

[0140] 2.4 Acceptance

[0141] In view of the particularity of oil and gas pressure pipelines, non-destructive methods should be used as much as possible in the acceptance of compression molding repairs.

[0142] 1. Non-destructive acceptance method

[0143] Moulding repair process control and moulding repair layer appearance acceptance

[0144] 2. Acceptance content

[0145] The non-destructive acceptance method is to check the following three aspects during and after the construction:

[0146] a. Moulded repair layer inspection;

[0147] b. The bonding performance between the molded repair layer and the base steel pipe;

[0148] c. Base steel pipe inspection.

[0149] The objects and requirements of acceptance inspection are shown in the following table:

[0150] Table 4 Inspection items for molded repair acceptance

[0151]

[0152]

[0153] 3. Treatment methods for molded repair layers that do not meet acceptance requirements

[0154] If the acceptance items in the above table do not meet the acceptance requirements, you can consider peeling off the entire molded repair layer and reinstalling a new molded repair layer;

[0155] 4. Hydrostatic pressure test

[0156] If conditions permit, the molding effect can be verified by an in-service hydrostatic test, that is, a pressure test is performed on the molded pipe.

[0157] Molded materials should be fully cured prior to hydrostatic testing.

[0158] The pressure of the hydrostatic test should not be lower than 1.0 times the normal operating pressure of the pipeline, and the pressure holding time should be at least 60 minutes. During the test, the changes in pressure and temperature should be recorded in detail. If pressure drop and leakage occur during the test, unless there is a special reason, the molding should be deemed invalid.

[0159] 5. Destructive acceptance method

[0160] According to the needs of the pipeline owner, the molded pipe can be cut off and the molding effect can be verified by the hydrostatic burst test. The purpose of the burst test is to cause the pipeline to rupture and fail. The burst test is carried out in accordance with the "Hydrostatic Burst Test Method for Transport Steel Pipe" (SY / T 5992-94).

[0161] a. Before the hydrostatic test, the molded repair layer should be fully cured;

[0162] b. During the hydrostatic test, the changes in pressure and temperature should be recorded in detail. If leakage occurs at the molded defect or the molded repair layer breaks and fails during the test, the molding should be deemed invalid.

[0163] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.

Claims

1. A macromolecular medium-weight repair agent, characterized in that: It includes component A and component B; The component A comprises 100-300 parts of epoxy resin, 10-100 parts of phenyl glycidyl ether, 1-20 parts of carboxyl liquid nitrile rubber, and 10-50 parts of boron carbide powder; The B component comprises 100-200 parts of polyamide resin, 50-150 parts of ethylenediamine, 1-20 parts of thiourea and 1-10 parts of triacetin.

2. A macromolecular repair agent according to claim 1, characterized in that: The epoxy resin in the component A is a resin with a medium epoxy value, and the boron carbide powder is a nano boron carbide powder; The preparation of the A component comprises the following steps: S1. Take 200 parts of a resin with a medium epoxy value and 50 parts of phenyl glycidyl ether; pour them into a reaction kettle with a constant temperature of 80°C, stir them thoroughly for 4 hours and keep the temperature constant for 30 minutes; S2, take 10 parts of carboxyl liquid nitrile rubber, set the temperature to 100°C, stir thoroughly for 3 hours, and then lower the temperature by 20°C every 2 hours; S3. After 6 hours, add 20 parts of nano boron carbide powder, keep the temperature at 40°C, stir for 2 hours, place in a defoaming box, keep the temperature at 40°C for 24 hours to eliminate excess bubbles, and complete the modulation process of component A.

3. A macromolecular repair agent according to claim 1, characterized in that: The polyamide resin in the B component is a low molecular weight polyamide resin; The preparation of the B component comprises the following steps: S1. Take 150 parts of low molecular weight polyamide resin and 100 parts of ethylenediamine, put them into a reaction kettle at one time, heat the temperature to 120°C, stir at medium speed, and stir for 4 hours; S2, naturally cool to 70-80°C, add 10 parts of thiourea and 5 parts of triacetin, keep the temperature at 70°C, and stir at medium speed; S3. When no ammonia odor escapes from the system, stop heating and stirring, cool to room temperature, discharge the material, and seal for storage, thus completing the preparation process of component B.

4. A macromolecular repair agent according to claim 1, characterized in that: When the repair agent is used, component A and component B are fully and evenly mixed in a ratio of 4 to 10:

1.

5. The oil and gas pipeline repair method using the repair agent according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Using ultra-high molecular weight polyethylene fiber material as the skeleton, design and determine the number of winding layers and molded thickness at the pipeline repair site; S2. Perform surface treatment on the pipe at the repaired part; S3, fully and evenly mix the components A and B of the repair agent, spread the ultra-high molecular weight polyethylene fiber material flat, and evenly apply the mixed repair agent on the ultra-high molecular weight polyethylene fiber material until the ultra-high molecular weight polyethylene fiber material is fully soaked; S4. Level the fully soaked ultra-high molecular weight polyethylene fiber material and wrap it around the outer surface of the pipe at the repaired part with appropriate force until the number of winding layers required by the construction design is reached; S5. Install the molding device to mold the wound parts. After the molding is completed and the molded layer is solidified, remove the molding device and conduct acceptance.

6. The oil and gas pipeline repair method according to claim 5, characterized in that: In the above-mentioned S1, an 8mm through hole is opened in the pipeline body to simulate the pressure bearing data of the molded repair layer on the pipeline medium after the failure of the pipeline body due to corrosion; the relationship between the molded thickness and the pressure bearing is calculated by the three-dimensional nonlinear finite element method, and then the number of winding layers and the molded thickness of the ultra-high molecular weight polyethylene fiber material are determined through a hydrostatic pressure blasting test.

7. The oil and gas pipeline repair method according to claim 5, characterized in that: In the above-mentioned S2, before surface treatment is performed on the pipeline at the repaired part, the defect points of the repaired part need to be verified, and the surface treatment of the pipeline can be performed only after the verification is consistent; the surface treatment of the pipeline includes stripping off the old anti-corrosion layer and polishing the pipeline surface.

8. The oil and gas pipeline repair method according to claim 5, characterized in that: In the above S4, before winding the ultra-high molecular weight polyethylene fiber material, a filling material is prepared and applied to the concave part of the steel pipe surface to repair the defective part until the surface is flat; the two sides of the weld root should be filled with the filling material to make the surface near the weld transition smoothly and avoid hollowing caused by the high weld when the ultra-high molecular weight polyethylene fiber material is wound; The filling material comprises component A, S-grade glass fiber and component B, component A: S-grade glass fiber: component B = 2:1.5:1, and component A, S-grade glass fiber and component B are fully mixed.

9. The oil and gas pipeline repair method according to claim 5, characterized in that: In the above S4, during the winding process, the axial overlap length of the ultra-high molecular weight polyethylene fiber material should be 20% to 40% of its width, and the circumferential overlap length should be not less than 200 mm; when the circumferential winding length is insufficient, the overlap length of the ultra-high molecular weight polyethylene fiber material to be wound should be not less than 200 mm.

10. The oil and gas pipeline repair method according to claim 5, characterized in that: In the S5, the molding device includes a tightening reel and a retaining ring. The tightening reel is wound on the pipe and pre-tightened by bolts. The retaining rings are arranged at both ends of the tightening reel to prevent the disorderly flow of the repair agent during the molding process. Before molding, a release agent is coated on the inner side of the retaining ring and the tightening reel.